2014
DOI: 10.1074/mcp.m113.034371
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Functional Reprogramming during Osteoclast Development Using Quantitative Proteomics and mRNA Profiling

Abstract: In addition to forming macrophages and dendritic cells, monocytes in adult peripheral blood retain the ability to develop into osteoclasts, mature bone-resorbing cells. The extensive morphological and functional transformations that occur during osteoclast differentiation require substantial reprogramming of gene and protein expression. Here we employ -omic-scale technologies to examine in detail the molecular changes at discrete developmental stages in this process (precursor cells, intermediate osteoclasts, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 93 publications
(117 reference statements)
4
42
1
Order By: Relevance
“…First, the previous study used clonal populations of RAW 264.7 cells deemed to possess high osteoclastogenic potential; using purified precursor cells could enrich for genes related to OC differentiation. Second, numerous studies have consistently shown that gene expression levels do not correlate well with protein abundance; this phenomenon could therefore contribute to the discrepancy between the correlation analyses based on cDNA levels versus protein levels . In line with this thought, we assessed the protein levels of housekeeping genes reported to be stable at the transcript level in OCs and found that transcript and protein levels for some of these genes were inconsistent (Fig.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…First, the previous study used clonal populations of RAW 264.7 cells deemed to possess high osteoclastogenic potential; using purified precursor cells could enrich for genes related to OC differentiation. Second, numerous studies have consistently shown that gene expression levels do not correlate well with protein abundance; this phenomenon could therefore contribute to the discrepancy between the correlation analyses based on cDNA levels versus protein levels . In line with this thought, we assessed the protein levels of housekeeping genes reported to be stable at the transcript level in OCs and found that transcript and protein levels for some of these genes were inconsistent (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…In BMMs, B2m was transiently upregulated, whereas Hprt was downregulated during OC differentiation; none of these proteins, however, were significantly altered in RAW264.7 cells. Because numerous studies have identified major discrepancies in the correlation between mRNA and protein expression levels, we were interested in whether housekeeping proteins exhibited any differences in OCs. In contrast to the findings by Stephens and colleagues, we observed that Gapdh levels were consistent throughout OC differentiation in BMMs, whereas B2m and Hprt were not, indicating that these two proteins may not be reliable internal controls for protein samples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study revealed that a number of proteins and molecular signaling pathways, including electron transport chain and oxidative phosphorylation pathways, were altered in RAW264.7 cells cultured in low serum compared to those cultured in the conventional 10 % culture system [ 13 ]. An et al have performed proteomics analysis to study the changes in global protein expression during osteoclastogenesis in conventional culture system [ 14 ]. However, to the best of our knowledge, the proteomic changes that occur in RAW 264.7 cells as they differentiate into osteoclasts in a low serum culture system has not been reported.…”
Section: Introductionmentioning
confidence: 99%